Endoscopic Ultrasonography‐Guided Fine Needle Aspiration Can Be Used to Rule Out Malignancy in Autoimmune Pancreatitis Patients. (3rd July 2017) - Sugimoto, Mitsuru; Takagi, Tadayuki; Suzuki, Rei; Konno, Naoki; Asama, Hiroyuki; Watanabe, Ko; Nakamura, Jun; Kikuchi, Hitomi; Waragai, Yuichi; Takasumi, Mika; Sato, Yuki; Hikichi, Takuto; et al.
Abstract : Objectives: The aim of this study was to review the suitability of endoscopic ultrasonography‐guided fine needle aspiration (EUS‐FNA) for ruling out malignancy in autoimmune pancreatitis patients. Methods: We retrospectively reviewed 40 autoimmune pancreatitis patients (type 1:37 patients; type 2: two patients; possible autoimmune pancreatitis: one patient) who received EUS‐FNA. Among the 40 autoimmune pancreatitis patients, 34 were not histopathologically diagnosed with autoimmune pancreatitis by EUS‐FNA, and they were followed up for more than 6 months in our hospital. Moreover, 14 pancreatic cancer patients who were not diagnosed by EUS‐FNA were selected as a control group. These 14 patients constituted 3.9% of the 360 pancreatic cancer patients who received EUS‐FNA. We evaluated the prognoses of the 34 autoimmune pancreatitis patients and the clinical differences between these 34 autoimmune pancreatitis patients and the 14 pancreatic cancer patients. Results: All 34 autoimmune pancreatitis patients showed reduced pancreatic swelling. The main pancreatic duct dilation ( > 3 mm), the diameter of the main pancreatic duct, the capsule‐like rim sign, and serum CA19‐9 levels were significantly different between the autoimmune pancreatitis and pancreatic cancer patients (2.9% versus 69.2%, P  < .01; 1.7 ± 1.6 mm versus 6.8 ± 5.0 mm, P  < .01; 79.4% versus 0%, P  < .01; 41.4 ± 79.0 U/mL versus 2079.1 ± 275.3 U/mL, P  = .02). Conclusions: Almost all pancreatic cancers can be diagnosed by EUS‐FNA. Furthermore, other clinical characteristics of pancreatic cancer undiagnosed by EUS‐FNA were different from autoimmune pancreatitis undiagnosed by EUS‐FNA. Endoscopic ultrasonography‐guided FNA can be used to rule out malignancy in autoimmune pancreatitis patients.